Definisi Gangguan Terhadap Objek Sewa dalam Perjanjian Sewa Menyewa - Syafa Nissa Amanda (Dinasti Review Publisher, 2024)
The law exists to accommodate the protection of the rights of every person, including but not limited to rights arising from rental agreements. A rental agreement is an effort that can be taken to maintain the rights between the lessor and the lessee. One of the problems that arise in a rental agreement is that the rental object is used as collateral by the lessor. Seeing this problem, the author will study it using doctrinal research methods by conducting studies based on statutory regulations. The aim of this research is to find out the legal steps that need to be taken in connection with the rental object being used as collateral.